PARTISIPASI MASYARAKAT DALAM KEGIATAN POSYANDU MAWAR DI DESA MUNENGWARANGAN KECAMATAN PAKIS KABUPATEN MAGELANG - Hidayat, Yayat (Universitas Insan Cendekia Mandiri, 2024)
The purpose of this study was to determine community participation in this case cadres and to find out the inhibiting factors and find solutions to the problems that hamper the activities of Posyandu Mawar. The method used in this research is descriptive method using a qualitative approach. Collecting data in this study is using interview and observation techniques. Community participation in this case is quite good for cadres as evidenced by the regular implementation of Posyandu Mawar activities, which is once a month on the second Tuesday of the week. The biggest inhibiting factor in this activity is the lack of funds owned by Posyandu Mawar Munengwarangan; Another inhibiting factor is the lack of support from community leaders, RW administrators and other institutions or activity programs in the community for Posyandu Mawar activities. In order for the Posyandu Mawar activities to be more developed and of better quality, there are suggestions; it is expected to increase public awareness including community leaders, RW administrators, and other institutions or activity programs so that they can participate and assist in terms of funding so that Posyandu Mawar activities will increase and be able to reach Strata Mandiri. It is hoped that there will be collaboration with stakeholders and there will be cadre regeneration and collaboration to form Joint Business Groups (KUB) to produce products so as to increase funds for Posyandu Mawar.